Trends in the gameplay of European football players - Soroka Andrzej (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2014)
Background: The aim of this study was to compare the effectiveness of footballers who participated in the 2008 and 2012 European Championships. The study was conducted by analysis of basic technical and tactical game.